Prezydencjalizacja zachowań wyborczych w elekcji parlamentarnej w 2015 roku - Peszyński, Wojciech (Political Preferences, 2016)
Presidentialization of Electoral Face in Polish Parliamentary Election in 2015 year In this article the author analyses the process by means of the quantitative and proportional distribution of answers regarding two questions. The first one concerns the leader effect and the second the social approval for television debates participated by the leaders of the two major political parties (the questions can be found next to the tables presenting the results of the study). In the research under consideration were used the same questions as in 2012 and 2013, when no nation-wide election was organized. The comparison of the results gathered in those “election-free” years and in 2015, when two important votings (presidential and parliamentary) took place may bring particularly interesting conclusions. Key words: presidentialisation, personalization, leader effect, electoral face, political parties